Impelentasi Tahap Penyusunan Organisasi Formal dalam Pengelolaan Lembaga Filantropi Rumah Zakat Sumatera Selatan - Robaiyadi, Robaiyadi; Suparto, Suparto (CV. ITTC INDONESIA, 2025)
This study aims to analyze the implementation of the formal organizational structuring stage in the management of Rumah Zakat South Sumatra as a zakat-, infaq-, and sadaqah-based (ZIS) philanthropic institution. Modern philanthropic institutions are required to possess organizational structures that are professional, accountable, and adaptive to social dynamics, including digitalization and the increasing demand for community empowerment. This study employs a descriptive qualitative approach, with data collected through interviews, observations, and documentation. The findings indicate that the stages of formal organizational structuring at Rumah Zakat South Sumatra include the formulation of objectives aligned with the institution’s national vision, the determination of activities based on core functions (fundraising, distribution and utilization, finance, and volunteer management), the grouping of activities through function-based departmentalization, the establishment of working relationships through coordination mechanisms and integrated information systems, and the implementation of a clear functional organizational structure. This study emphasizes the importance of formal organization as a fundamental instrument in strengthening the governance of philanthropic institutions, particularly in the context of managing public funds that demand high levels of transparency and professionalism. Keywords: Formal organization, philanthropy, organizational structure, institutional governance.